REVEREND ROBOT: AUTOMATION AND CLERGY: with Mohammad Yaqub Chaudhary, "Augmented Reality, Artificial Intelligence, and the Re‐Enchantment of the World"; and William Young, "Reverend Robot: Automation and Clergy.". - Young, William (Zygon: Journal of Religion & Science, 2019)
Digital technology, including artificial intelligence, is having a dramatic impact on the professions of medicine, law, journalism, finance, and others. Some suggest that clergy will also be affected. We describe recent progress in designing artificially intelligent systems, suggesting that this is possible, perhaps even likely. We investigate ways in which technology currently is affecting ministry and outline some plausible scenarios in which digital systems could supplement or supplant clergy in some areas, specifically preaching and pastoral care. We also raise some theological issues raised by the use of digital systems in ministry.